2001
DOI: 10.1038/sj.bjp.0704227
|View full text |Cite
|
Sign up to set email alerts
|

Block by gabapentin of the facilitation of glutamate release from rat trigeminal nucleus following activation of protein kinase C or adenylyl cyclase

Abstract: The e ect of activation of protein kinase C (PKC) or adenylyl cyclase on release of glutamate has been investigated in a perfused slice preparation from the rat caudal trigeminal nucleus. Stimulation of PKC by phorbol 12-myristate 13-acetate (PMA) produced a concentration-dependent increase in K + -evoked release of [ 2 H]-glutamate (maximum increase 45%, EC 50 11.8 nM), but in the presence of gabapentin (30 mM) the facilitation of release was blocked. The adenylyl cyclase activator forskolin (FSK) also induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 23 publications
1
54
0
1
Order By: Relevance
“…Although the antinociceptive mechanisms of spinal gabapentin remain unclear, several hypotheses have been suggested. It has been reported that gabapentin decreases glutamate concentrations and inhibits the release of glutamate and glutamatergic synaptic transmission presynatically (15)(16)(17). Glutamate acts on the NMDA receptor and non-NMDA receptor and shows the excitatory effect (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although the antinociceptive mechanisms of spinal gabapentin remain unclear, several hypotheses have been suggested. It has been reported that gabapentin decreases glutamate concentrations and inhibits the release of glutamate and glutamatergic synaptic transmission presynatically (15)(16)(17). Glutamate acts on the NMDA receptor and non-NMDA receptor and shows the excitatory effect (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of whether this effect is due to a direct action of gabapentin on brainstem structures or is secondary to a spinal or a peripheral action of gabapentin remains unanswered. Although an antihyperalgesic action of gabapentin has only been demonstrated at the level of the dorsal horn or the subnucleus caudalis (its functional equivalent in the trigeminal system) (57)(58)(59), the hypothesis of a direct gabapentin effect on brainstem structures is reasonable, because spinobulbo-spinal circuits are contributing to experimental central sensitization. Accordingly, gabapentin has been demonstrated to have ubiquitous effects in the central nervous system (e.g., refs.…”
Section: Gabapentin Modulation Of Fmri Brain Responses: Antihyperalgesicmentioning
confidence: 99%
“…Also, it is likely that the rate of cycling of ␣ 2 ␦ subunits is variable in different cell types, at different locations within the cell, and depending on the physiological state of the cell. For instance, it has been reported that GBP acutely reduced glutamate release in trigeminal neurons only after activation by protein kinase C (Maneuf and McKnight, 2001). Interestingly, protein kinase C activation has been shown to lead to an increased insertion of calcium channels of the Ca v 2 family at the plasma membrane (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%